Phenological control of vegetation biophysical feedbacks to the regional climate - Lingxue Yu; Ye Liu; Fengqin Yan; Lijie Lu; Xuan Li; Shuwen Zhang; Jiuchun Yang (Geography and Sustainability)
Phenology shifts influence regional climate by altering energy, and water fluxes through biophysical processes. However, a quantitative understanding of the phenological control on vegetation’s biophysical feedbacks to regional climate remains elusive. Using long-term remote sensing observations and Weather Research and Forecasting (WRF) model simulations, we investigated vegetation phenology changes from 2003 to 2020 and quantified their biophysical controls on the regional climate in Northeast China. Our findings elucidated that earlier green-up contributed to a prolonged growing season in forests, while advanced green-up and delayed dormancy extended the growing season in croplands. This prolonged presence and increased maximum green cover intensified climate-vegetation interactions, resulting in more significant surface cooling in croplands compared to forests. Surface cooling from forest phenology changes was prominent during May’s green-up (-0.53 ± 0.07 °C), while crop phenology changes induced cooling throughout the growing season, particularly in June (-0.47 ± 0.15 °C), July (-0.48 ± 0.11 °C), and September (-0.28 ± 0.09 °C). Furthermore, we unraveled the contributions of different biophysical pathways to temperature feedback using a two-resistance attribution model, with aerodynamic resistance emerging as the dominant factor. Crucially, our findings underscored that the land surface temperature (LST) sensitivity, exhibited substantially higher values in croplands rather than temperate forests. These strong sensitivities, coupled with the projected continuation of phenology shifts, portend further growing season cooling in croplands. These findings contribute to a more comprehensive understanding of the intricate feedback mechanisms between vegetation phenology and surface temperature, emphasizing the significance of vegetation phenology dynamics in shaping regional climate pattern and seasonality.